Nauczanie gramatyki języka obcego a podejście zadaniowe - Pawlak, Mirosław (Neofilolog, 2021)
While there is a consensus that teaching grammar is now indispensable in most educational contexts, there still exist numerous controversies as to how this should most beneficially be done. They concern, among others, such issues as the choice of instructional options to be used in order to introduce and practice grammar structures or to provide corrective feedback on errors made in the use of such structures (cf. Loewen, 2020; Nassaji, 2017; Pawlak, 2014, 2020a). On a more general level, a question arises as to the optimal way of organizing the material to be taught, with consequences for the overall approach to grammar instruction. One influential alternative to a structural syllabus, in which case grammar structures are carefully preselected and sequenced, is task-based language teaching, which can be conceptualized and implemented in various ways (cf. Ellis, 2017, 2018). The paper discusses the role of grammar in the task-based approach, also taking into account techniques and procedures that can be employed for this purpose. An overview of existing empirical evidence will be presented and an attempt will be made to highlight the way in which communicative tasks can be used to assist grammar teaching in the Polish educational context.